Whole-Exome Sequencing Reveals Rare Germline Mutations in Patients With Hemifacial Microsomia - Chen, Xiaojun; Liu, Fatao; Mar Aung, Zin; Zhang, Yan; Chai, Gang (Frontiers in Genetics, 2021)
Hemifacial microsomia (HFM) is a rare congenital disease characterized by a spectrum of craniomaxillofacial malformations, including unilateral hypoplasia of the mandible and surrounding structures. Genetic predisposition for HFM is evident but the causative genes have not been fully understood. Thus, in the present study, we used whole-exome sequencing to screen 52 patients with HFM for rare germline mutations. We revealed 3,341 rare germline mutations in this patient cohort, including those in 13 genes previously shown to be associated with HFM. Among these HFM-related genes, NID2 was most frequently mutated (in 3/52 patients). PED4DIP, which has not been previously associated with HFM, exhibited rare variants most frequently (in 7/52 patients). Pathway enrichment analysis of genes that were mutated in ˃2 patients predicted the “laminin interactions” pathway to be most significantly disrupted, predominantly by mutations in ITGB4, NID2, or LAMA5. In summary, this study is the first to identify rare germline mutations in HFM. The likely disruptions in the signaling pathways due to the mutations reported here may be considered potential causes of HFM.